A new species of the genus Ovophis Burger in Hoge & Romano-Hoge, 1981 (Serpentes, Viperidae) from southern Yunnan, China - Shuo Liu; Mian Hou; Mingzhong Mo; Mei Li; Biao Li; Xiong Luo; Dingqi Rao; Song Li (ZooKeys)
A new species of Ovophis is described from Yuanyang Guanyinshan Provincial Nature Reserve in southern Yunnan Province, China. The new species can be distinguished from congeneric species by the following combination of characters: ratio of tail length to total length 0.191–0.206, internasals separated by one or two scales, dorsal scales in 22-21-17 rows, ventrals 146–148, subcaudals 57–64, most subcaudals paired and a few unpaired, third supralabial larger than fourth, white spots on dorsal tail continuous. This study further reveals that the species diversity of Ovophis has been seriously underestimated, and there is still a lot of work to be done on the taxonomy of this genus.